Outcomes of pediatric liver transplantation in inherited metabolic diseases: a single-center's experience - Yilmaz, T. U.; Ertekin, V.; Keceoglu, S.; Ersoy, M.; Ozer, A.; Citak, A.; Karakayali, H.; Emiroglu, R. (LIPPINCOTT WILLIAMS \& WILKINS, 2022)
Joint Annual International Congress of ILTS, ELITA and LICAGE, Istanbul, TURKEY, MAY 04-07, 2022